The Effect of Good Corporate Governance and Capital Structure on Firm Value with Financial Performance as an Intervening Variabel - Syafitri, Shinta; Putra, Wirmie Eka; Jumaili, Salman (East Asian Journal of Multidisciplinary Research, 2024)
With financial performance serving as an intervening variable case study of retail companies listed on the Indonesia Stock Exchange in 2019–2022, the goal of this research is to ascertain the impact of sound corporate governance and capital structure on firm value. There were forty-two retail companies in the study's population. Of the 42 companies that used the purposive sampling approach for sample withdrawals, 29 of them satisfied the sample requirements. Secondary data was obtained by obtaining the annual report of the firm via the website of the Indonesia Stock Exchange or the company itself, together with the documentation data gathering process. Using SmartPLS software, the partial least square (PLS) analysis of structural equation modeling, which is component- or variance-based, is combined with descriptive analysis to analyze the data. The findings demonstrated that capital structure and sound corporate governance both have an impact on a company's value. Financial performance is not able to mediate the relationship between excellent corporate governance and capital structure on company value, but neither do good corporate governance nor capital structure have any effect on financial performance.